Studies on Protein Folding, Stability and Amyloid Formation/Dissociation: Effect of Selected Biomolecules. - Kundu, Debanjan (IIT(BHU) Varanasi, 2022)
Abstract is available in the attachment.
This Thesis is summitted Debanjan Kundu a Ph.D. Scholar of IIT(BHU) Varanasi.
Keywords: Protein; Folding; Amyloid; Formation; Biomolecules